2015
DOI: 10.1101/cshperspect.a019398
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Compensation inDrosophila

Abstract: SUMMARYDosage compensation in Drosophila increases the transcription of genes on the single X chromosome in males to equal that of both X chromosomes in females. Site-specific histone acetylation by the malespecific lethal (MSL) complex is thought to play a fundamental role in the increased transcriptional output of the male X. Nucleation and sequence-independent spreading of the complex to active genes serves as a model for understanding the targeting and function of epigenetic chromatin-modifying complexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 132 publications
4
182
0
Order By: Relevance
“…X upregulation is best documented in Drosophila males to increase expression of a large portion of genes [74]. In organisms where dosage adjustment is sex-specific - as in Drosophila - there would be no need for adjustment in the homogametic sex.…”
Section: Dosage Compensation Between Sex Chromosomes and Autosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…X upregulation is best documented in Drosophila males to increase expression of a large portion of genes [74]. In organisms where dosage adjustment is sex-specific - as in Drosophila - there would be no need for adjustment in the homogametic sex.…”
Section: Dosage Compensation Between Sex Chromosomes and Autosomesmentioning
confidence: 99%
“…In Drosophila , upregulation of the male X chromosome is achieved by recruitment of the MSL complex to increase levels of H4K16 acetylation and open chromatin, which results in increased transcription initiation and elongation (Fig. 1) [74]. Recruitment of the MSL complex to the male X is mediated by a 2–4 fold enrichment in specific binding motifs.…”
Section: Molecular Evidence Of X Upregulationmentioning
confidence: 99%
“…There are three general methods by which this can be performed: first, a twofold up-regulation in the expression of X-linked gene in males; second, a twofold down-regulation of genes on each of the two X chromosomes in females; and finally, the complete inactivation of one of the two X chromosomes in females. The first strategy has been adopted in the fruit fly, Drosophila (see Lucchesi and Kuroda 2014), the second in the worm Caenorhabditis elegans (see Strome et al 2014), and, it now seems, both the first and the last in mammals.…”
Section: Overviewmentioning
confidence: 99%
“…The general feasibility of Ohno's suggestion was established by work on dosage compensation in the fruit fly Drosophila melanogaster in which genetic, biochemical, and recent high-throughput gene expression studies have confirmed that dosage compensation occurs through upregulation of X-linked genes in XY males (discussed in Lucchesi and Kuroda 2014). Crucially, the mechanism that evolved in the fly is such that up-regulation occurs only in males, circumventing the problem of overexpression in XX females.…”
Section: Solving the Male Problem: Up-regulation Of X-linked Genesmentioning
confidence: 99%
“…MOF was originally identified in Drosophila as a component of the protein complexes known as male-specific lethal (MSL) (1, 2), which is only found in male flies, and the non-specific lethal (NSL) complex (35), which is found in both male and female flies. In Drosophila, MOF was initially found to function in dosage compensation whereby transcription of genes on the single male X-chromosome must be increased two-fold relative to females who have two X-chromosomes.…”
Section: Introductionmentioning
confidence: 99%